Analisis Kualitas Website Salatiga Virtual Library Tour Dalam Memenuhi Kebutuhan Informasi Bagi Pengguna - Henggar Penggalih Cahyaningtias; Nurlistiani (Pustabiblia: Journal of Library and Information Science, 2026)
The digital transformation in the field of libraries during the Covid-19 pandemic has accelerated the development of websites as the main medium for delivering public information and services quickly and without boundaries. Library websites, such as the Salatiga Virtual Library Tour developed by the Salatiga City Library and Archives Office in collaboration with CV. Heikel Media Cipta Solusi, serve as a significant platform for providing broad access to library information and digital resources. Therefore, this study aims to analyze the quality of the Salatiga Virtual Library Tour website in meeting users' information needs and to identify various challenges faced by the Salatiga City Library and Archives Office in its development. This research applies a qualitative method with a descriptive approach through observation, interviews, and documentation techniques. Based on Shedroff's theoretical framework, the findings reveal that the Salatiga Virtual Library Tour website successfully presents informative, accessible, and responsive content. However, regular content updates, better data management, improved visual design, and the development of interactive and accessibility features are still needed to make the website more inclusive, engaging, and beneficial for all community segments. The search system functions well but is not yet integrated with the OPAC or collections beyond the local content. Access limitations are often related to third-party issues and rental system constraints. Major challenges include cyber-attacks, server disruptions, and limited human resources in website management. This study highlights that adequate technological and human resource support is crucial to maintain service quality and data security, enabling the website to provide optimal and inclusive information access for its users.